Evaluation of dimethoate toxicity on fertilization and on embryonic development of Paracentrotus lividus (Lamarck, 1816). Issue 4 (12th August 2020) - Scalisi, Elena Maria; Pecoraro, Roberta; Salvaggio, Antonio; Corsaro, Aurora; Messina, Giuseppina; Ignoto, Sara; Lombardo, Bianca Maria; Brundo, Maria Violetta
Abstract: Organophosphates are a large class of chemicals with anticholinesterase action insecticides. Dimethoate belongs to the class of organophosphates and it is used for agriculture purpose. Its main toxicological role in animals and humans is the inhibition of the activity of acetylcholinesterase. Although it is not considered genotoxic, carcinogenic and teratogen, there is evidence of increased pup mortality in developmental neurotoxicity studies. Since there is scant published literature about developmental toxicity, we investigated the adverse effects of dimethoate on fertilization and embryonic development in sea urchin ( Paracentrotus lividus ), a model organism widely used to assess the toxicity of contaminants on environmental matrices; so pesticide residues can be released into the environment, and could affect the health of organisms, including humans. Different solution of dimethoate (4 × 10 −3, 4 × 10 −4, 4 × 10 −5, 4 × 10 −6 and 4 × 10 −7 g/10 ml) have been tested on spermatozoa of P. lividus to evaluate the fertilizing ability of them when we added egg cells untreated. We demonstrated that dimethoate does not interfere with fertilizing ability of spermatozoa but egg cells fertilized by treated spermatozoa showed alterations in the segmentation planes as asymmetric and/or asynchronous cell divisions.